PERAN BADAN PENGAWAS PEMILIHAN UMUM DALAM MENINGKATKAN NETRALITAS APARATUR SIPIL NEGARA PADA PEMILIHAN KEPALA DAERAH KOTA MAKASSAR TAHUN 2020 - Nurul Ismi, Andi Putri; Malik, Ihyani; Riskasari, Riskasari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The General Election Organizing Body, is an institution in charge of supervising every stage of the General Election or Pilkada either before or after the election process is held. One of the important aspects supervised by Bawaslu is related to the Neutrality of the State Civil Apparatus (ASN). Each stage of the pilkada process becomes one of the focuses of Bawaslu's supervision. The research method used in this research is qualitative. The results of this study indicate that the supervision of Bawaslu in increasing the neutrality of ASN in Makassar City is in accordance with Law Number 7 of 2017 concerning the duties and authorities of Bawaslu and Perbawaslu No. 6 of 2016 of ASN regarding the neutrality of ASN, members of the TNI and POLRI. Thus, this study can conclude that Bawaslu's supervision of ASN in Makassar City has been carried out in accordance with applicable regulations as evidenced by several findings that have been followed up with recommendations to KASN as the institution authorized to act on violations found. Thus, this study explains how the role of Bawaslu in increasing the neutrality of ASN.